2020
DOI: 10.48550/arxiv.2010.12666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proton and neutron form factors with quark orbital excitations

Yu. A. Simonov

Abstract: Nucleon form factors play an especially important role in studying the dynamics of nucleons and explicit structure of the wave functions at arbitrary nucleon velocity. The purpose of the paper is to explain theoretically all four nucleon form factors measured experimentally in the cross section measurements (by the Rosenbluth method), yielding almost equal normalized form factors G p E , G p M , G n M ), as well as in the polarization transfer experiments, where a strongly decreasing proton electric form facto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Assuming an exact Lorentz contracted form for the wave functions participating in the same matrix element with different velocities it was found that meson form factors well reproduce experimental data [32],and the same is true for the baryon form factors at least for moderate Q values [33]. Finally the same LC effect helps to understand the strong ρ decays [34]. It is a purpose of this paper to understand better the effects of LC in different physical systems in the whole range of Q values and for this purpose we consider the case of the hadron-hadron scattering with the one hadron exchange.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Assuming an exact Lorentz contracted form for the wave functions participating in the same matrix element with different velocities it was found that meson form factors well reproduce experimental data [32],and the same is true for the baryon form factors at least for moderate Q values [33]. Finally the same LC effect helps to understand the strong ρ decays [34]. It is a purpose of this paper to understand better the effects of LC in different physical systems in the whole range of Q values and for this purpose we consider the case of the hadron-hadron scattering with the one hadron exchange.…”
Section: Introductionmentioning
confidence: 68%
“…In this respect it is interesting what happens with the momentum dependent wave function when it experiences a Lorentz boost. As it was discussed in [2,3,4,5,7,8,9,11,12,27,28,29,30,31,32,33,34] and below in this paper,the x-space and p-space (pseudo)scalar q q wave functions moving with the velocity v have the form…”
Section: The Qualitative Discussion Of the Perturbative Vs Lorentz Co...mentioning
confidence: 90%
“…does not contain any internal angular momenta of the quarks, which can influence the Q dependence of the form factors. It is clear that the ground states of the 3q system have in the dominant component the wave function ψ(ρ), which is called the hypercentral approximation in the framework of the hyperspherical approach, developed in [18], originally in nuclear physics, and was used in the relastivistic formalism with the relativistic Hamiltonian in [19] to calculate the baryon masses [19], the magnetic moments [20], and the form factors [21] in good agreement with experimental data.…”
mentioning
confidence: 84%
“…We also define the corresponding momentum variables: q = ∂ i∂ξ , k = ∂ i∂η , and also the proton wave functions in the momentum space in the simple Gaussian form, which is close to the wave function, calculated in [19,20,21] for protons and neutrons:…”
mentioning
confidence: 99%